2018
DOI: 10.4183/aeb.2018.315
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Reduces Seizure Burden and Hippocampal Injury in a Rat Model of Perinatal Asphyxia

Abstract: Context. Foetal asphyxia, a frequent birth complication, detrimentally impacts the immature brain, resulting in neuronal damage, uncontrolled seizure activity and long-term neurological deficits. Oxytocin, a neurohormone mediating important materno-foetal interactions and parturition, has been previously suggested to modulate the immature brain's excitability, playing a neuroprotective role. Our aim was to investigate the effects of exogenous oxytocin administration on seizure burden and acute brain injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…This was followed by an almost linear and much slower (0.0086 pH units/min) secondary recovery phase lasting until 15 min post-asphyxia. We did not observe an alkaline overshoot of the kind described in P6 rats with steady asphyxia induced by 9 % O 2 and 20 % CO 2 (Helmy et al, 2012(Helmy et al, , 2011, suggesting that fast brain pH recovery in itself is sufficient in triggering seizures following asphyxia (see also Panaitescu et al, 2018).…”
Section: Dependence Of the Post-asphyxia Increase In Neuronal Excitabsupporting
confidence: 52%
“…This was followed by an almost linear and much slower (0.0086 pH units/min) secondary recovery phase lasting until 15 min post-asphyxia. We did not observe an alkaline overshoot of the kind described in P6 rats with steady asphyxia induced by 9 % O 2 and 20 % CO 2 (Helmy et al, 2012(Helmy et al, , 2011, suggesting that fast brain pH recovery in itself is sufficient in triggering seizures following asphyxia (see also Panaitescu et al, 2018).…”
Section: Dependence Of the Post-asphyxia Increase In Neuronal Excitabsupporting
confidence: 52%
“…Given the higher plasma values observed in children with milder forms of ASDs, it may be hypothesised that their increased responsiveness to the behavioural therapy might be, at least partly, mediated through oxytocinergic mechanisms (46). Oxytocin's involvement in the GABA-switch from excitatory to inhibitory neurotransmitter at birth might substantiate the importance of its appropriate regulation for typical brain development (47,48). The correlations observed with other neuropeptide levels suggest that these substances might be inter-connected in terms of potential effectiveness in the administration of adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As such, preserving a low [Cl − ] i could be associated with higher cellular viability. We have previously shown that chloride transport modulation in immature hippocampal cultures has a neuroprotective effect both in vitro during OGD [24], as well as in an in vivo model of perinatal asphyxia [25]. Considering that mature neurons display altered chloride gradients under stroke conditions, which may also be influenced by many pharmaceutical agents used in stroke patients, there is an increased interest to determine the potentially favorable or detrimental effects of modulating chloride gradients.…”
Section: Introductionmentioning
confidence: 99%